Stylistic Analysis of Langston Hughes’ Selected Poems - Hersh Mohamad Mohamad Amin; Suhayla H. Majeed (Zanco Journal of Humanity Sciences)
The scope of this paper is limited to the Stylistics Analysis of Langston Hughes’ three selected poems under the titles of “Dream Deferred”, “Justice”, and “The Negro Speaks of Rivers”. The analysis is carried out under the aspect of phonological, lexical and semantic levels. The aim of this study is to discover the Stylistic devices the poet has used in his poems to enhance his message as well as to express to his community and the world his ideas, concerns and observation on socio-political issues. Also, to get better understanding of the message he is trying to convey.